Risk factors for a low weight gain in the early stage of adolescent anorexia nervosa inpatient treatment: findings from a pilot study - Knoll-Pientka, Nadja; Bühlmeier, Judith; Peters, Triinu; Albrecht, Muriel; Adams, Frederike; Wustrau, Katharina; Teufel, Martin; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity)

Clinical Trials Required to Assess Potential Benefits and Side Effects of Treatment of Patients With Anorexia Nervosa With Recombinant Human Leptin - Hebebrand, Johannes; Milos, Gabriella; Wabitsch, Martin; Teufel, Martin; Führer, Dagmar; Bühlmeier, Judith; Libuda, Lars; Ludwig, Christine; Antel, Jochen (Frontiers in Psychology)

Estimation of Nematic Order Parameters via Haller Analysis of 1H NMR Spectra of Liquid Crystals - Tang, Ming-xue; Schmidt, Claudia (Chinese Journal of Magnetic Resonance)
The Haller relationship was applied to estimate the nematic order parameter S from 1H NMR spectra of fully protonated liquid crystals aligned in the magnetic field. The NMR line shapes were approximated as doublets of very broad peaks. Both the temperature-dependent doublet Splitting and the full width at half maximum of the whole spectra were used for Haller extrapolation. The order parameters obtained with the proposed approach for 4-cyano-4'-pentylbiphenyl (5CB) and the nematic mixture E7 were found to be in good agreement with previously reports.
Keywords: nematic liquid crystal; order parameter; Haller analysis; 1H NMR

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Vorerfahrungen, Einstellungen und motivationale Orientierungen als mögliche Einflussfaktoren auf den Einsatz digitaler Werkzeuge im naturwissenschaftlichen Unterricht - Vogelsang, Christoph; Finger, Alexander; Laumann, Daniel; Thyssen, Christoph (Zeitschrift für Didaktik der Naturwissenschaften)

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan

Reflexionskompetenz trainieren: Unterrichtsvideographie als Werkzeug zur fachdidaktischen Begleitung im Praxissemester - Vogelsang, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Midinfrared Birefringence of Liquid Crystals, Polarimetry, and Intensity Modulators - Atorf, Bernhard; Auf der Landwehr, Chris Holm; Rennerich, Roman; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)

Den Einsatz digitaler Medien im naturwissenschaftlichen Unterricht lehren - Untersuchung der Lehrinitiative Didaktik:digital im Spannungsfeld von standortübergreifender Wirkungsanalyse und standortspezifischer Evaluation - Vogelsang, Christoph (Hochschuldidaktik erforscht Qualität - Profilbildung und Wertefragen in der Hochschulentwicklung III)

Integrated transition edge sensors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Gerrits, Thomas; Lita, Adriana; Krapick, Stephan; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Mirin, Richard; Nam, Sae Woo; Silberhorn, Christine; Bartley, Tim (APL Photonics)

Durchgängige Sprachbildung und Inklusion in der sachunterrichtsdidaktischen Lehrer*innenbildung. Eine interdisziplinäre Evaluationsstudie mit Sachunterrichtsstudierenden - Blumberg, Eva; Niederhaus, Constanze; Albers, Timm; Havkic, Amra (Inklusion im Sachunterricht)

Low-Temperature Plasma-Enhanced Atomic Layer Deposition of Tin(IV) Oxide from a Functionalized Alkyl Precursor: Fabrication and Evaluation of SnO2-Based Thin-Film Transistor Devices - Mai, Lukas; Zanders, David; Subaşı, Ersoy; Ciftyurek, Engin; Hoppe, Christian; Rogalla, Detlef; Gilbert, Wolfram; de los Arcos de Pedro, Maria Teresa; Schierbaum, Klaus; Grundmeier, Guido; Bock, Claudia; Devi, Anjana (ACS Applied Materials & Interfaces)

Potential Precursor Alternatives to the Pyrophoric Trimethylaluminium for the Atomic Layer Deposition of Aluminium Oxide - Mai, Lukas; Boysen, Nils; Zanders, David; de los Arcos de Pedro, Maria Teresa; Mitschker, Felix; Mallick, Bert; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana (Chemistry – A European Journal)

Surface modification of ZnMgAl-coated steel by dielectric-barrier discharge plasma - Knust, Steffen; Kuhlmann, Andreas; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (RSC Advances)
Correlation between atmospheric DBD plasma-induced surface chemical changes on a ZnMgAl alloy coating and the resulting adhesive properties.

Fabrication of Lyotropic Alignment Layers for Thermotropic Liquid Crystals Facilitated by a Polymer Template - Zhang, Bingru; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried (Advanced Optical Materials)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Improved organic thin-film transistor performance by dielectric layer patterning - Temme, Julian; Meyers, Thorsten; Reker, Julia; Vidor, Fábio F.; Vollbrecht, Joachim; Kitzerow, Heinz-Siegfried; Paradies, Jan; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Pawel Pieranski – crystallographer of liquids and Alfred-Saupe-prize laureate 2019 - Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Trendbericht Organische Chemie - Andexer, Jennifer N.; Beifuss, Uwe; Beuerle, Florian; Brasholz, Malte; Breinbauer, Rolf; Ernst, Martin; Gulder, Tobias A. M.; Kath‐Schorr, Stephanie; Kordes, Markus; Lehmann, Matthias; Lindel, Thomas; Lüdeke, Steffen; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Transfer hydrogenation of cyclic carbonates and polycarbonate to methanol and diols by iron pincer catalysts - Liu, Xin; de Vries, Johannes G.; Werner, Thomas (Green Chemistry)
The reduction of poly and cyclic carbonates in the presence of an earth abundant metal catalyst using isopropanol as the hydrogen donor is reported.
Keywords: Pollution; Environmental Chemistry

Life Cycle Assessment for the Organocatalytic Synthesis of Glycerol Carbonate Methacrylate - Büttner, Hendrik; Kohrt, Christina; Wulf, Christoph; Schäffner, Benjamin; Groenke, Karsten; Hu, Yuya; Kruse, Daniela; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Organocatalytic Chlorination of Alcohols by P(III)/P(V) Redox Cycling - Longwitz, Lars; Jopp, Stefan; Werner, Thomas (The Journal of Organic Chemistry)
Keywords: Organic Chemistry

Polyethers as Complexing Agents in Calcium-Catalyzed Cyclic Carbonate Synthesis - Hu, Yuya; Steinbauer, Johannes; Stefanow, Vivian; Spannenberg, Anke; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Phosphetane Oxides as Redox Cycling Catalysts in the Catalytic Wittig Reaction at Room Temperature - Longwitz, Lars; Spannenberg, Anke; Werner, Thomas (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Catalytic Approaches to Monomers for Polymers Based on Renewables - Stadler, Bernhard M.; Wulf, Christoph; Werner, Thomas; Tin, Sergey; de Vries, Johannes G. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

The Mitsunobu reaction, reimagined - Longwitz, Lars; Werner, Thomas (Science)
Catalytic nucleophilic substitution of alcohols makes organic synthesis greener
Keywords: Multidisciplinary

Catalytic Systems for the Synthesis of Biscarbonates and Their Impact on the Sequential Preparation of Non-Isocyanate Polyurethanes - Wulf, Christoph; Reckers, Matthias; Perechodjuk, Anna; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Reduction of Activated Alkenes by P III /P V Redox Cycling Catalysis - Longwitz, Lars; Werner, Thomas (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Herstellung von Wellenleitern aus Materialien der KTP-Familie - Padberg, Laura; Eigner, Christof; Santandrea, Matteo; Silberhorn, Christine

Kooperatives Arbeiten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven Unterricht in der Grundschule. Posterpräsentation auf der 54. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik und Bildungsforschung – Fremde Schwestern?“ - Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Effects of Interprofessional Collaboration in Inclusive Education of Pre-Service Primary School Teachers and Special Education Teachers on their Self-Concepts. Poster Presentation. ECER 2019 (European Conference on Educational Research). “Education in an Era of Risk – the Role of Educational Research for the Future“ - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Kooperativ Lernumgebungen für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule gestalten – ein Forschungs- und Entwicklungsprojekt zur Förderung von Grund- und Förderschullehrkräften (KLinG). Posterpräsentation auf der 28. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts e. V. (GDSU) - Mester, Theresa; Blumberg, Eva; Kirsch, Alexander; Hellmich, Frank; Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Schwab, Susanne

Preparing Pre-service Teachers’ Team-Teaching Processes in Inclusive Science Education in Primary Schools. Poster Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hoya, Fabian Karl; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Curved Polar Dibenzocoronene Esters and Imides versus Their Planar Centrosymmetric Homologs: Photophysical and Optoelectronic Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Externally Controlled Lotka-Volterra Dynamics in a Linearly Polarized Polariton Fluid - Pukrop, Matthias; Schumacher, Stefan (arXiv:1903.12534)
Spontaneous formation of transverse patterns is ubiquitous in nonlinear dynamical systems of all kinds. An aspect of particular interest is the active control of such patterns. In nonlinear optical systems this can be used for all-optical switching with transistor-like performance, for example realized with polaritons in a planar quantum-well semiconductor microcavity. Here we focus on a specific configuration which takes advantage of the intricate polarization dependencies in the interacting optically driven polariton system. Besides detailed numerical simulations of the coupled light-field exciton dynamics, in the present paper we focus on the derivation of a simplified population competition model giving detailed insight into the underlying mechanisms from a nonlinear dynamical systems perspective. We show that such a model takes the form of a generalized Lotka-Volterra system for two competing populations explicitly including a source term that enables external control. We present a comprehensive analysis both of the existence and stability of stationary states in the parameter space spanned by spatial anisotropy and external control strength. We also construct phase boundaries in non-trivial regions and characterize emerging bifurcations. The population competition model reproduces all key features of the switching observed in full numerical simulations of the rather complex semiconductor system and at the same time is simple enough for a fully analytical understanding of the system dynamics.

Preparing Pre-service Teachers’ Team-Teaching Processes in Inclusive Science Education in Primary Schools. Poster Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hoya, Fabian Karl; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

Pre-service Primary School Teachers’ Preparation for Team-Teaching in Inclusive Schools. Poster Presentation. 18th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2019. „Thinking Tomorrows’s Education: Learning from the past, in the present and for the future" - Hoya, Fabian Karl; Löper, Marwin Felix; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Molecular Doping of PCPDT-BT Copolymers: Comparison of Molecular Complexes with and Without Integer Charge Transfer - Dong, Chuan-Ding; Schumacher, Stefan
Molecular doping in conjugated polymers is a crucial process for their application in organic photovoltaics and optoelectronics. In the present work we theoretically investigate p-type molecu- lar doping in a series of (poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b”]dithiophene)-alt- 4,7-(2,1,3-benzothiadiazole)] (PCPDT-BT) conjugated oligomers with different lengths and three widely-used dopants with different electron affinities, namely F4TCNQ, F6TCNNQ, and CN6-CP. We study in detail the molecular geometry of possible oligomer-dopant complexes and its influence on the doping mechanisms and electronic system properties. We find that the mechanisms of dop- ing and charge transfer observed sensitively depend on the specific geometry of the oligomer-dopant complexes. For a given complex different geometries may exist, some of which show transfer of an entire electron from the oligomer chain onto the dopant molecule resulting in an integer-charge transfer complex, leaving the system in a ground state with broken spin symmetry. In other ge- ometries merely hybridization of oligomer and dopant frontier orbitals occurs with partial charge transfer but spin-symmetric ground state. Considering the resulting electronic density of states both cases may well contribute to an increased electrical conductivity of corresponding film samples while the underlying physical mechanisms are entirely different.

Depth camera based statistical shape fitting approach for the creation of an individualized lower body biomechanical model: validity and reliability - Taetz, Bertram; Teufl, Wolfgang; Weidmann, Alexander; Pietschmann, Juliane; Jöllenbeck, Thomas; Bleser, Gabriele (Computer Methods in Biomechanics and Biomedical Engineering)
Keywords: Computer Science Applications; Human-Computer Interaction; Biomedical Engineering; General Medicine; Bioengineering

A von Hamos-type hard X-ray spectrometer at the PETRA III beamline P64 - Kalinko, Aleksandr; Caliebe, Wolfgang A.; Schoch, Roland; Bauer, Matthias (Journal of Synchrotron Radiation)
The design and performance of the high-resolution wavelength-dispersive multi-crystal von Hamos-type spectrometer at PETRA III beamline P64 are described. Extended analyzer crystal collection available at the beamline allows coverage of a broad energy range from 5 keV to 20 keV with an energy resolution of 0.35–1 eV. Particular attention was paid to enabling two-color measurements by a combination of two types of analyzer crystals and two two-dimensional detectors. The performance of the spectrometer is demonstrated by elastic-line and emission-line measurements on various compounds.
Keywords: Instrumentation; Nuclear and High Energy Physics; Radiation

Gold(ii) in redox-switchable gold(i) catalysis - Veit, Philipp; Volkert, Carla; Förster, Christoph; Ksenofontov, Vadim; Schlicher, Steffen; Bauer, Matthias; Heinze, Katja (Chemical Communications)
Gold(ii) species catalyse the cyclisation of N(2-propyn-1-yl)benzamide to 2-phenyl-5-vinylidene-2-oxazoline without halide abstraction while the neutral gold(i) complex is inactive indicating a gold(ii/i) redox-switch.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Wie können Studierende des Lehramts an Grund- und Förderschulen auf das kooperative Arbeiten in der inklusiven Grundschule vorbereitet werden? Posterpräsentation auf der 7. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Entwicklung kooperativen Arbeitens bei Lehramtsstudierenden für den naturwissenschaftlichen Sachunterricht in der inklusiven Grundschule. Posterpräsentation auf dem 8. Paderborner Grundschultag - Löper, Marwin Felix; Görel, Gamze; Hoya, Fabian Karl; Kirsch, Alexander; Mester, Theresa; Schulze, Jan Roland; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Controllable high-speed polariton waves in a PT-symmetric lattice - Ma, Xuekai; Kartashov, Yaroslav Y; Gao, Tingge; Schumacher, Stefan (New Journal of Physics)

Efficient C-band single-photon upconversion with chip-scale Ti-indiffused pp-LiNbO3 waveguides - Xie, Zhenda; Luo, Kai Hong; Chang, Kai Chi; Panoiu, Nicolae C.; Herrmann, Harald; Silberhorn, Christine; Wong, Chee Wei (Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Estimating the Indistinguishability of Heralded Single Photons Using Second-Order Correlation - Faruque, Imad I.; Sinclair, Gary F.; Bonneau, Damien; Ono, Takafumi; Silberhorn, Christine; Thompson, Mark G.; Rarity, John G. (Physical Review Applied)
Keywords: General Physics and Astronomy

Improving Selectivity and Activity of CO2 Reduction Photocatalysts with Oxygen - Kreft, Stefanie; Schoch, Roland; Schneidewind, Jacob; Rabeah, Jabor; Kondratenko, Evgenii V.; Kondratenko, Vita A.; Junge, Henrik; Bauer, Matthias; Wohlrab, Sebastian; Beller, Matthias (Chem)
Keywords: Materials Chemistry; Biochemistry (medical); General Chemical Engineering; Environmental Chemistry; Biochemistry; General Chemistry

Exercise-Induced Changes of Multimodal Interactions Within the Autonomic Nervous Network. - Vieluf, S; Hasija, Tanuj; Jakobsmeyer, Rasmus; Schreier, PJ; Reinsberger, Claus (Front Physiol)

Invertible Micelles Based on Ion-Specific Interactions of Sr2+ and Ba2+ with Double Anionic Block Copolyelectrolytes - Carl, Nico; Prévost, Sylvain; Schweins, Ralf; Houston, Judith E.; Morfin, Isabelle; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Phase Transformation Behavior of Polylactide Probed by Small Angle Light Scattering and Calorimetry - Schmidt, Nico; Keuker‐Baumann, Susanne; Meyer, Jörg; Huber, Klaus (Journal of Polymer Science Part B: Polymer Physics)
Keywords: Materials Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics